2019
DOI: 10.4102/sajhrm.v17i0.1123
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived organisational support, organisational commitment and turnover intention among employees in a selected organisation in the aviation industry

Abstract: Orientation: Turnover intention, a precursor of employee turnover, comprises some of the challenges experienced by the 21st-century organisation – the aviation industry has not been spared.Research purpose: The primary goal of this study was to conduct an analysis of the relationships between perceived organisational support (POS), organisational commitment and turnover intention at a selected organisation within the aviation industry.Motivation for the study: Relatively, little attention has been directed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
1
22
0
4
Order By: Relevance
“…Several studies concurred with these findings and demonstrated that when employees feel valued by an organisation, they develop feelings of attachment to that organisation (Tumwesigye, 2010). Scott ( 2014) and Satardien's (2014) studies made similar findings in a South African context.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Several studies concurred with these findings and demonstrated that when employees feel valued by an organisation, they develop feelings of attachment to that organisation (Tumwesigye, 2010). Scott ( 2014) and Satardien's (2014) studies made similar findings in a South African context.…”
Section: Discussionmentioning
confidence: 66%
“…Our study, however, examined organisational commitment as a consequence of POS. Previous studies that extensively investigated the relationship between POS and employee organisational commitment (Satardien 2014;Scott, 2014; suggest that POS is important for organisations because it is linked to higher levels of employee commitment. In other words, supported employees are likely to increase their effort, demonstrate organisational citizenship behaviours, and identify with the organisation's goals and objectives (Scott, 2014;Tumwesigye, 2010).…”
Section: Consequences Of Posmentioning
confidence: 99%
“…One South African research found that workplace spirituality (Kokt & Palmer, 2019), work-life balance and friendship (Coetzee, Ferreira, & Potgieter, 2019) and remuneration (Bussin & Brigman, 2019) were predictors of affective commitment. Another South African study established that perceived organisational support was a predictor of affective commitment (Satardien, Jano, & Mahembe, 2019). In Tshwane municipality, it was established that employee engagement was a variable that predicted employees' affective commitment (Maleka, Mpofu, Hlatywayo, Meyer, Carr, & Parker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the determinant factors of Organisational Support (OS) can be described as the beliefs of employees about the degree to which the company values its commitment and cares about its well-being (Eisenberger et al, 2004;Satardien et al, 2019). The OS itemsincludedemployer understanding, assisting withfamily-friendly, responsive,improveskills and on-job training,treatedwithtrust and respect.…”
Section: Research Conceptual Model and Hypothesesmentioning
confidence: 99%